Generation and Characterization of Specific Monoclonal Antibodies and Nanobodies Directed Against the ATP-Gated Channel P2X4 - Bergmann, Philine; Garcia de Paco, Elvira; Rissiek, Björn; Menzel, Stephan; Dubberke, Gudrun; Hua, Jennifer; Rassendren, François; Ulmann, Lauriane; Koch-Nolte, Friedrich (Frontiers in Cellular Neuroscience, 2019)
The P2X4 channel is involved in different physiological and pathological conditions and function in the nervous system. Despite the existence of several mouse models for which the expression of the gene was manipulated, there are still little information on the expression of the protein at cellular level. Particularly, supposedly specific available antibodies often proved to recognize unrelated proteins in P2X4-deficient mice. Here, we used an in vivo DNA vaccine approach to generate a series of monoclonal and nanobodies specific for human, mouse and rat P2X4 channels. We further characterized these antibodies and show that they solely recognize the native form of the proteins both in biochemical and cytometric applications. Some of these antibodies prove to specifically recognize P2X4 channels by immunostaining in brain or sensory ganglia slices, as well at cellular and subcellular levels. Due to their clonality, these different antibodies should represent versatile tools to further characterize the cellular functions of P2X4 in the nervous system as well as at the periphery.